P Penerapan Motif Kuta Mesir Dalam Penciptaan Produk Kriya Kayu Studio Tatto - I Gede Bagus Arya Kusuma; I Made Suparta; I Nyoman Ngidep Wiyasa (Pusat Penerbitan LP2MPP ISI Denpasar, 2021)
Tattoo studio is one of the places that is very much in demand by foreign guests, the general public and teenagers as a place for tattoos. In addition, the tattoo studio must also have good standards if you want to receive guests comfortably when visiting the studio for tattoos. In the process of making tattoos, apart from tools or tattoo machines, there are also several supporting products to support the needs of tattoo artists while working. Some of the supporting products found in the tattoo studio such as beds, chairs, tables to put tattoo equipment, and lamps mostly use aluminum which looks simple. This need for novelty is very interesting to be reviewed and realized in the form of works using wood by applying kuta mesir motifs as a source of inspiration in order to create a new atmosphere. The problems to be solved in the creation of this final project are: (1) about are the processes and techniques for the realization of the tattoo studio wood craft produc (2) kuta mesir decorative motifs will be applied to the tattoo studio's wood craft products (3) the process of finishing the tattoo studio craft product, The method used in the creation of this work uses SP theory. Gustami are the three pillars of creation including exploration, design and realization. The result of this creation process is a bed, chair, and lamp. This work was created aiming to add diversity to the design of the tattoo studio product.